Islam, crime and criminal justice - Spalek, Basia (Willan, 2002)
This book brings together research into key aspects of the interconnections between Islam, crime and the criminal justice system in Britain, a particularly timely collection in the light of both the recent disturbances in several northern English cities as well as the impact of the events of 11 September 2001 and their aftermath. Chapters in the book focus on young Muslim men and criminal activity, Muslim women and their experiences of victimisation, the experiences of Muslim police officers, of Muslims in prison, issues of human rights in relation to Muslims in Britain, and the criminal justi